Adopting Mindfulness During Worship Scale as the Khusyu’ Measurement for Indonesian Muslims - Muhammad Fakhruddin Al-Razi; Imam Amrusi Jailani; Triyanti Nurkhikmah (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Khusyu’, as the core of devotion and even religion, has not been given enough attention in behavior measurement research. This study aims to adapt the Mindfulness during Worship Scale (MWS) to measure khusyu'. By formulating measurable dimensions and objective indicators, this research will make the quality of khusyu' easier to measure. It can provide the foundation for future research on what factors contribute to and hinder the attainment of khusyu' in prayer. A pilot study was conducted with 220 respondents from four age groups (15 - 20, 21 - 25, 26 - 30, and over 30). Three levels of analysis were conducted: item, construct, and theory level. The results indicate that the MWS-adapted items are valid when applied to all respondents, but not to 15-20 and 21-25. The reliability analysis showed an acceptable value (0.715) for the whole sample. However, variations were observed between the different age groups. However, the results of the CFA indicated an invalid model. Factor analysis also showed that adapted MWS items clustered into four distinct factors. In theory, the MWS can be applied to the cognitive domain and, to some extent, the emotional aspect, but it does not adequately capture the psychomotor dimension of khusyu'. Further research is needed to develop a theoretically robust and statistically valid measurement framework that includes cognition, emotion, and psychomotor dimensions and applies to all ages.